Thrombus aspiration in acute coronary syndromes: prevalence, procedural success, change in serial troponin T levels and clinical outcomes in a contemporary Swiss cohort. Issue 6 (1st September 2018) - Aghlmandi, Soheila; Schärer, Nadine; Heg, Dik; Räber, Lorenz; Zwahlen, Marcel; Gencer, Baris; Nanchen, David; Carballo, David; Carballo, Sebastian; Jüni, Peter; von Eckardstein, Arnold; Landmesser, Ulf; et al.
Abstract: Background: Randomised controlled trials have provided conflicting results regarding procedural and clinical outcomes of thrombus aspiration combined with percutaneous coronary intervention, when compared with primary percutaneous coronary intervention alone in patients with acute coronary syndromes. Methods: Acute coronary syndrome patients referred for coronary angiography to four Swiss university hospitals between 2009 and 2012 were enrolled in the SPUM–ACS cohort. At the discretion of the interventional cardiologist, patients underwent thrombus aspiration with percutaneous coronary intervention or percutaneous coronary intervention alone. Procedural success was defined as post-procedural thrombolysis in myocardial infarction III flow in the infarct-related artery. Serial changes in high-sensitivity troponin T (ΔhsTnT) and adjudicated 30 days (1 year) clinical events defined as the composite of cardiac death, recurrent myocardial infarction or clinically indicated coronary revascularisation were assessed. Results: Among 1641 patients, 777 (47.4%) had angiographic evidence of coronary thrombus. Patients were categorised into thrombus aspiration with percutaneous coronary intervention ( n =663) or percutaneous coronary intervention alone ( n =114). ST-segment elevation myocardial infarction (STEMI) patients more often received thrombus aspiration with percutaneous coronary intervention (87.8%) than non-STEMI patients (73.5%), P <0.001. Procedural success was not different in thrombus aspiration with percutaneous coronary intervention compared with percutaneous coronary intervention alone (93.8% vs. 90.7%, P =0.243). ΔhsTnT was similar in STEMI patients (3.09±4.52 vs. 2.19±4.92 µg/l, P =0.086) as was clinical outcome in the entire cohort at 30 days (2.9% vs. 3.6%, P =0.76) and 1 year (7.2% vs. 5.3%, P =0.55) regardless of whether thrombus aspiration was used during primary percutaneous coronary intervention or not. Conclusions: In this real-world acute coronary syndrome cohort, patients treated by thrombus aspiration with percutaneous coronary intervention showed no difference in the restoration of coronary blood flow compared with percutaneous coronary intervention alone immediately after the procedure. Furthermore, ΔhsTnT and clinical outcomes at either 30 days or 1 year were similar between thrombus aspiration with percutaneous coronary intervention or percutaneous coronary intervention alone. Clinical Trials Registration: SPUM–ACS cohort NCT01000701